Olanzapine in the treatment of pervasive developmental disorders: a case series analysis - Stavrakaki, Chrissoula (2004)
Controlling the symptoms that are characteristic of patients with pervasive developmental disorders is often challenging. We report on the safety and efficacy of olanzapine in the treatment of 7 patients with pervasive developmental disorders. The patients were all male and ranged in age from 8 to 52 years. They received olanzapine doses of 5–10 mg/d along with their various other drug regimens. Patients were monitored and evaluated for a mean duration of 17.7 (range 12–26) months while on olanzapine therapy. Very few side effects were observed during treatment. All patients showed clinically significant improvement on the Clinical Global Impressions scale, as well as an improved score as measured by the Global Assessment of Functioning scale. Our observations support the use of long-term olanzapine therapy for symptom control in patients with pervasive developmental disorders.